HPLC METHOD DEVELOPMENT FOR THE ANALYSIS OF BISOPROLOL IN COMBINED DOSAGE FORM CONTAINING BISOPROLOL AND ENALAPRIL AND IN VITRO DISSOLUTION STUDIED - Logoyda, Liliya; Kovalenko, Sergiy; Abdel-Megied, Ahmed M.; Zhulkevych, Igor; Drapak, Iryna; Demchuk, Inna; Netsyuk, Oleh (International Journal of Applied Pharmaceutics, 2019)
Objective: A simple, rapid and reproducible HPLC method was developed for the determination of bisoprolol in experimental combined dosage forms containing bisoprolol and enalapril and for drug dissolution studies. Methods: A C18 column (Hi Qsil C18, 5 μm, 4.6х250 mm) and a mobile phase methanol: phosphate buffer solution (65:35, v/v) mixture were used for separation and quantification. Analyses were run at a flow rate of 1.0 ml/min and at ambient temperature. The injection volume was 300 μL and the ultraviolet detector was set at 225 nm. The method was validated as per ICH guidelines. Results: Under these conditions, bisoprolol was eluted at 4.75 min. Total run time was shorter than 6 min. A linear relationship between the concentration and the area of ​​chromatographic peaks of bisoprolol in the range of 0.625 mg/ml-5.000 mg/ml (3.750 mg/ml at pH 1.2) has been established. In the medium with pH 1.2 release of bisoprolol from tablets in 5 min is 38.42%, and after 15 min-85.51%, in medium with pH 4.5 the release of bisoprolol from tablets in 5 min makes 59.78%, and after 15 min-103.71%; in a medium with pH 6.8, the release of bisoprolol from tablets in 5 min is 61.29%, and after 15 min-85.90%. Conclusion: The developed method was applied successfully for quality control assay of bisoprolol in experimental tablets and in vitro dissolution studies.